Casein-maltodextrin Maillard conjugates encapsulation enhances the antioxidative potential of proanthocyanidins: An in vitro and in vivo evaluation. (1st June 2021) - Sun, Xianbao; Wu, Xuejiao; Chen, Xiangyu; Guo, Rui; Kou, Yuxing; Li, Xujiao; Sheng, Yi; Wu, Yan
Highlights: Maillard conjugates encapsulated Proanthocyanidins (PAs) as novel antioxidants. Antioxidant activity of PAs was protected by encapsulation during storage and heat. Encapsulated PAs prolong lifespan of C. elegans by upregulating SOD and CAT activities. Maillard conjugates encapsulation enhanced the bioaccessibility of PAs. Abstract: Practical application of proanthocyanidins (PAs) as antioxidants is limited because of their hard-to-maintained activities during the processes and storage and in severe gastrointestinal environments. To overcome this challenge, we have developed an easy and green method to encapsulate PAs based on casein-maltodextrin Maillard conjugates. The current work entails the systematic study on the antioxidative potentials of fabricated casein-maltodextrin-PAs nanoparticles (CMPNs). In vitro antioxidant activities of CMPNs remained well during storage in 28 days and treatments under 40–80 °C. In vivo Caenorhabditis elegans ( C. elegans ) model further showed that the CMPNs could prolong the lifespan of nematodes and protected nematodes from oxidative stress and heat shock. Analyses of intracellular superoxide dismutase and catalase activities also confirmed the existence of an antioxidant protective effect. Besides, in vitro release test showed that the encapsulation enhanced the bioaccessibility of PAs. These results have important implications for the development of novel antioxidants in nutraceutical industries.